Hearing Loss - Sataloff, Robert Thayer; Roehm, Pamela C. (CRC Press, 2025)
"Covering all aspects of the anatomy, physiology, diagnosis, and treatment of hearing loss, this Fifth Edition is an accessible and comprehensive text for anyone interested in expanding their knowledge of hearing loss. This update includes new material including cochlear biology, synaptopathy, and advances in audiometry and aural rehabilitation. Chapters such as 'Sudden Hearing Loss' and 'Facial Paralysis' have been expanded with updated material, and readers will gain a deeper understanding of important principles through the benefit of the many case reports included. Additionally, four appendices provide summaries of more detailed anatomical topics which will prove useful for trainees and students. General practitioners, nurses, audiometric technicians and any other professionals (both clinical and non-clinical) will find this a useful resource on the topic of hearing loss. This new edition is also an ideal tool for students' exam revision"--